Dakwah dalam Bisnis dan Enterpreneur Nabi Muhammad SAW - Gusriani, Raden Yani; Faulidi, Haris (Alhadharah: Jurnal Ilmu Dakwah, 2012)
One aspect of the life of Muhammad who received less serious attention is his leadership in the field of business and entrepreneurship. Most of his life before he became the messenger of Allah was as a businessman. Very distinctive characteristics of the business activities carried out by the Prophet were honesty and trustworthy in keeping his word. Among the many aspects of his business that deserves to be exemplified in business interactions are maintaining the values of dignity, honor, and glory. For him, business is not only limited to the velocity of money and goods, but more that it preserves self-respect.